AB0587 Limitations of the 1990 American College of Rheumatology Criteria in the Classification of Cutaneous Vasculitis. Study of 773 Cutaneous Vasculitis. (10th June 2014) - Ortiz-Sanjuán, F.; Blanco, R.; Pina, T.; Calvo-Río, V.; Loricera, J.; Martín, L.; Άlvarez, L.; González-Vela, M.C.; Rueda-Gotor, J.; González-Lόpez, M.A.; Peirό, M.E.; Santos-Gόmez, M.; et al.
Abstract : Background: In 1990 The American College of Rheumatology (ACR) established criteria for the classification of vasculitis. Cutaneous vasculitis (CV) comprises a wide and heterogeneous group of entities. Objectives: Our aim was to revise the usefulness of ACR-1990 criteria in classifying patients with CV. Methods: Retrospective study of a wide and unselected series of patients with CV from a single university hospital from January 1976 to January 2012. Patients were classified according to the 1990 ACR methodology and criteria. Results: 773 Patients (351 women/422 men) with a mean age of 34.1±27.4 years were diagnosed as having CV. Applying the 1990 ACR criteria patients were classified as secondary to connective tissue diseases (n=35), major infections (n=27), malignancies (n=16), mixed essential cryoglobulinemia (n=13), Wegener Granulomatosis (n=3), Churg-Strauss syndrome (n=3) and Polyarteritis nodosa (n=3). The remaining 673 patients were classified as Hipersensitivity vasculitis (n=247; 36.6%) or Henoch Schönlein Purpura (n=414; 61.4%). Disappointingly, 127 (18.8%) met criteria for both entities and 12 out of 673 cases did not meet criteria for HV nor HSP and were not classified. Conclusions: The ACR-1990 criteria for vasculitis do not properly classify patients with CV. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3111